Private metropolis : the eclipse of local democratic governance - Judd, Dennis R.; McKenzie, Evan; Alexander, Alba (Globalization and community, 2021)
"Examines the complex ecology of quasi-public and privatized institutions that mobilize and administer many of the political, administrative, and fiscal resources of today's metropolitan regions"--